Pengaruh Pembiayaan Kredit Usaha Rakyat Bank Rakyat Indonesia Terhadap Pendapatan UMKM di Talang Babat - Nano Romansyah; Zaenal Abidin; Ahmad Edi Saputra; Erwina Kartika Devi (Journal of Innovative and Creativity, 2025)
This study was conducted to determine the effect of People's Business Credit (KUR) financing on MSME income in Talang Babat and the extent of this influence. This study employed quantitative research. The results concluded that empirical hypothesis testing showed that the partial t-test showed a positive and significant effect of KUR financing on MSME income, amounting to 0.000, which is much smaller than the 0.05 level of significance, and a calculated t-value of 6.076 > 1.660. Therefore, Ho is rejected and Ha is accepted. The coefficient of determination (R2) was 0.266, indicating that KUR financing impacted MSMEs in Talang Babat by 26.6%, while the remaining 73.4% was influenced by other variables.